Hubungan Kualifikasi Petugas Filing dengan Ketepatan Penyimpanan Rekam Medis di RS Bhayangkara Polda DIY - Aria Dani, Ika, Ibnu Mardiyoko, SKM., MM, Dwi Astuti, SKM., M.Kes (2015)
Outpatient services in Bhayangkara Hospital have constraints in terms of availability of medical records late on-site service. This is due to an error in the storage of medical records by filing officer . Filing officer has a different background and qualifications are not all in accordance with the standards of competence of medical and health information recorder . This resulted in an error in the medical record storage . The purpose of this study is to determine the relationship between qualifications filing officer with record-keeping accuracy. This study uses survey design methods with cross sectional approach . The population of the study subjects were all officers of filing are 5 people and the population of the object is a medical record . Sampling with quota sampling method , the object sample of 15 medical records of each officer . Test using the chi-square statistic is computerized . The results showed that there was a correlation between level of education and accuracy of medical record storage (p ≤ 0.05) , there is a link between long working with record-keeping accuracy (p ≤ 0.05) and there was no relationship between participation in training medical record accuracy medical record storage (p > 0.05).